Angiomyofibroblastoma of the vulva: A case report and review of the literature - Samia Sassi; Chaimaa Nadim; Rihane El Mohtarim; Lamiae Rouas; Mounia Yousfi; Najat Lamalmi; Fatima El. Hassouni (Elsevier, 2024)
Angiomyofibroblastoma (AMFB) represents a rare, benign mesenchymal tumor with a predilection for the vulvovaginal region. It is usually diagnosed in middle-aged women. Histopathology and immunohistochemical study remain the key to diagnosis. Like other benign mesenchymal vulval tumors, AMFB shows indolent behavior and rarely recurs after complete surgical excision. Herein, we present a case of vulvar AMFB in a 51-year-old woman to highlight the diagnostic difficulties when considering this rare entity.